School Bullying and Post-traumatic Stress Disorder Symptoms: The Role of Parental Bonding - Plexousakis, Stefanos Stylianos; Kourkoutas, Elias; Giovazolias, Theodoros; Chatira, Kalliopi; Nikolopoulos, Dimitrios (Frontiers in Public Health, 2019)
Much research on school bullying and victimization have outlined several individual, family, and school parameters that function as risk factors for developing further psychosocial and psychopathological problems. Bullying and victimization are interrelated with symptoms of psychological trauma, as well as emotional/ behavioural reactions, which can destabilize psychosocial and scholastic pathways for children and adolescents. The current study explored the various dimensions of psychological trauma (depressive symptoms, somatization, dissociation, avoidance behaviours) associated with school bullying/victimization in relation to parental bonding among 433 students (8–16 years old) from representative large cities in Greece. The following scales were employed: (a) Olweus Bully/Victim Questionnaire, (b) Child Report of Post-traumatic Symptoms (CROPS), and (c) Parental Bonding Inventory instrument (PBI). Pathways analysis extracted a series of models which showed that maternal and paternal overprotection (anxious-controlling/aggressive) had positive association with post-traumatic stress symptoms. Specifically, the quality of parental bonding was related with children's bullying/victimization experiences and post-traumatic symptomology. Conversely, results indicated that maternal and paternal care can reduce the manifestation of post-traumatic stress symptoms. Implications for interventions are discussed.